1957
DOI: 10.1099/00221287-17-3-718
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Action of Phenanthridines: The Effect of Ethidium Bromide on Cell Division and Nucleic Acid Synthesis

Abstract: SUMMARY : The action of 2 : 7-diamino-9-phenyl-10-ethyl phenanthridinium bromide (ethidium bromide) on the parasitic flagellate Strigomonas oncopelti has been studied. The drug is irreversibly active only against growing organisms. Addition of the drug to cultures of organisms in the logarithmic phase of growth did not result in an immediate inhibition of growth but in a progressive decrease in growth rate; at least a doubling in number of organisms always occurred before multiplication finally ceased. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

1964
1964
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 13 publications
2
29
0
3
Order By: Relevance
“…The fact that T. rhodesiense multiplies more rapidly than T. congolense in the mouse suggests that the compounds might be removed more quickly to the secondary binding sites in the former species if they interfere with deoxyribonucleic acid metabolism, as homidium does in Strigomonas oncopelti (Newton, 1957(Newton, , 1964.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that T. rhodesiense multiplies more rapidly than T. congolense in the mouse suggests that the compounds might be removed more quickly to the secondary binding sites in the former species if they interfere with deoxyribonucleic acid metabolism, as homidium does in Strigomonas oncopelti (Newton, 1957(Newton, , 1964.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the hypothesis put forward by Newton (1957) to explain uptake of homidium by Strigomonas oncopelti, a greater rate of uptake of the three compounds by T. rhodesiense compared with T. congolense could be due to a differential affinity of the compounds for the primary binding sites of the two species, to their unequal rate of removal to the secondary binding sites, or to a combination of both these factors. The fact that T. rhodesiense multiplies more rapidly than T. congolense in the mouse suggests that the compounds might be removed more quickly to the secondary binding sites in the former species if they interfere with deoxyribonucleic acid metabolism, as homidium does in Strigomonas oncopelti (Newton, 1957(Newton, , 1964.…”
Section: Resultsmentioning
confidence: 99%
“…produces dyskinetoplasia in hemoflagellates (Newton, 1957(Newton, , 1964Steinert, 1969) . Mcllwain (1941) demonstrated that adenine interferes with acr's effects in bacteria .…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance of the B strain could be raised to 480 ng/ml EB, if the amount of hemin in medium C were doubled to 40,ug/ml . Thus, hemin played a role in the mode of action of a second agent known to cause dyskinetoplasia in hemoflagellates (Newton, 1957(Newton, , 1964Steinert, 1969 ;Steinert et al ., 1969) . From the B strain, cultures were obtained that were resistant both to 470 ng/ml acr and 260 ng/ml EB together (A-B strain) .…”
Section: Table IXmentioning
confidence: 99%
“…It was of interest to determine whether the drug could supply R. TOMCHICK AND H. G. MANDEL information on similar compartmentation in micro-organisms. The compound had been shown to inhibit DNA synthesis preferentially in a trypanosomal flagellate (Newton, 1957), and to depress RNA and DNA formation to a greater extent than that of protein in yeast cells (Kerridge, 1958). The drug's actions were therefore evaluated in a Gram-positive organism, Bacillus cereus, and a Gram-negative organism, Escherichia coli, in an effort to uncover dissociation of biosynthetic processes during inhibition of growth.…”
Section: Introductionmentioning
confidence: 99%